Shakespeare and the resistance : the Earl of Southampton, the Essex Rebellion, and the poems that challenged Tudor tyranny /: the Earl of Southampton, the Essex Rebellion, and the poems that challenged Tudor tyranny. (2018) - Asquith, Clare
No abstract available